Transdisciplinary research and sustainability
1 online resource (328 pages)
Keywords: "Transdisciplinarity is a new way of scientifically meeting the challenges of sustainability. Indeed, interdisciplinary collaboration and co-operation with non-academic 'practice partners' is at the core of this; creating contextualised, socially relevant knowledge about complex real-world problems. Transdisciplinary Research and Sustainability breaks new ground by presenting transdisciplinary research in practice, drawing on recent advances by the vibrant transdisciplinary research communities in the German-speaking world. It describes methodological innovations developed to address wide-ranging contemporary issues including climate change adaptation, energy policy, sustainable agriculture and soil conservation. Furthermore, the authors reflect on the challenges involved in integrating non-academic actors in scientific research, on the tensions that arise in the encounter of theory and praxis, and on the inherently normative, political nature of sustainability research. Highlighting the need for academic institutions to be transformed to reflect transdisciplinarity, this timely volume will appeal to postgraduate students and postdoctoral researchers interested in fields such as Sustainability Science, Transdisciplinary Studies and Philosophy of Science."--Provided by publisher.